PENGARUH KUALITAS PELAYANAN PETUGAS TERHADAP KEPUASAN PENGUNJUNG DI OBJEK WISATA SEJARAH BENTENG MARLBOROUGH DI KOTA BENGKULU - Pratama, Handika Fikri (JURNAL EKOMBIS REVIEW, 2016)
Handika  Fikri  Pratama;  This  research  is  intended  to  know  the  influence  of  service  quality (Reliability, Responsiveness, Assurance, Empathy and Tangibles) either partially or simultaneously to the satisfaction of customers and to know the more dominant influence from quality service. This research used quantitative method. There were 100 samples collected using accidental sampling. Collected using questioner and documentation. Instrument test is done by validity and reliability test. Multiple linear regression and classical assumption test used as analysis test. Hypothesis test is done by F test and t test.Result of this research shows take value  of value Reliability, Responsiveness, Assurance, Empathy and Tangibles variable have significant influence to dependent variable (Y) simultaneously. Tangibles don?t have significant influence to variable (Y) Partially. Reliability, Responsiveness, Assurance and Empathy variable have significant influence to dependent variable (Y). The value of determination coefficient (R Square) 97,6% it means that the independent variable may describe the dependent variables, while the remaining 2,4% is explained by the other independent variables which are not included in the this research.Keywords : Service Quality, Customer?s Satisfactions.